Iron-Catalyzed Tandem Radical Addition/Cyclization: Highly Efficient Access to Methylated Quinoline-2,4-diones - Sun, Huan; Jiang, Yue; Lu, Ming-Kun; Li, Yun-Yun; Li, Li; Liu, Ji-Kai (Synlett, 2020)
A visible-light-induced and iron-catalyzed oxidative radical addition/cyclization cascade reaction of N-(o-cyanoaryl)acrylamides with dimethyl sulfoxide has been developed. The method exhibits a wide substrate scope and an excellent functional-group tolerance, thus providing an efficient and convenient access to a variety of methylated quinoline-2,4-diones.
Keywords: photochemical reaction; iron catalysis; methylation; quinolinediones; cascade reaction